2020
DOI: 10.1007/s11307-020-01486-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fever on 18F-FDG Distribution In Vivo: a Preliminary Study

Abstract: Purpose: Elevated body temperature might change glucose metabolism in human organs. The purpose of this study is to explore 18 F-FDG distribution in febrile patients on the day of 18 F-FDG PET/CT scanning and compare it with patients with a normal temperature. Procedures: 18 F-FDG PET/CT was performed on 69 febrile patients and 82 patients with a normal temperature. Patient sociodemographic data, blood glucose levels before PET/CT, body temperature on the day of the exam, and laboratory test results were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…These findings underline again the correlation of both BM and splenic uptake in cases of systemic inflammation. In this scenario, a correlation between splenic and BM uptake with CRP has also been reported when focusing on patients with fever 14 . Furthermore, Rosenblum et al 15 .…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…These findings underline again the correlation of both BM and splenic uptake in cases of systemic inflammation. In this scenario, a correlation between splenic and BM uptake with CRP has also been reported when focusing on patients with fever 14 . Furthermore, Rosenblum et al 15 .…”
Section: Discussionmentioning
confidence: 79%
“…when focusing on patients with fever. 14 Furthermore, Rosenblum et al 15 reported a positive significant correlation for 18 F-FDG splenic uptake and CRP both at 1 and 2 h PET/CT scans, focusing only on LVV in a time-specific setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic resonance imaging (MRI) has the capability to visualize the three‐dimensional structure of tissue due to high spatial resolution and deep tissue penetration without radiation. [ 10 ] However, the sensitivity of MRI is relatively poor compared with positron emission tomography (PET) [ 11 ] and optical imaging, [ 12 ] resulting in a weak contrast resolution in distinguishing tumors from adjacent normal tissues. [ 13 ] Two strategies can be used to circumvent these limitations: (1) develop a nano‐system that can load high amount of magnetic resonance contrast agents, and (2) enhance the accumulation of magnetic nanoparticles in the tumor via an active targeting process, such as by employing a receptor‐ligand interaction mechanism during the delivery process.…”
Section: Introductionmentioning
confidence: 99%